RELATIONSHIP OF KNOWLEDGE OF PREGNANT MOTHERS WITH PREVENTING BEHAVIOR OF COVID-19 INFECTION AT PUSKESMAS GRABAG 1 - Inthan Amira Audhinia; Heni Setyowati ER; Eka Sakti Wahyuningtyas (Universitas Respati Yogyakarta, 2023)
Pregnant women are a group of people who are vulnerable to health problems. Physiologically, pregnant women experience a decrease in the immune system, this is probably due to an adjustment in the body of pregnant women to babies who are semi-allogenic tissues. Information about COVID-19 during pregnancy that can interfere with the health of pregnant women is still very limited. The pandemic period is very important to break the chain of virus transmission and protect those who are at risk of contracting the virus, which can be done individually by always maintaining personal hygiene independently or in groups through social distancing. That one of the factors of behavior is knowledge. Knowledge that a person has affected behavior, the better a person's knowledge, the better his behavior. Objective: The purpose of this study was to determine the relationship between knowledge of pregnant women and the COVID-19 prevention behavior. Methods: The design of this study was descriptive correlative with a cross-sectional approach. The sample of this study amounted to 86 respondents with a sample collection technique using random sampling. The research instrument used was the Covid-19 knowledge questionnaire to measure the level of knowledge of Covid-19 and prevention behavior. Statistical test using Spearman statistical test, this research has passed the Ethical clearance test with ethical number 194/KEPK.FIKES/ll.3.AU/2021. Results: The results of this study using the Spearman statistical test, based on the data obtained, it shows that there is a relationship between the knowledge of pregnant women about Covid-19 and the behavior of preventing transmission of Covid-19 infection. at the Grabag 1 Public Health Center with p-value = 0.650 and r = 0.212.